مفهوم العنصرية ومرتكزات علاجها في كليات رسائل النور لبديع الزمان سعيد النورسي - الشريفين، عماد عبدالله محمد (جامعة الشارقة, 2013)
تهدف الدراسة إلى بيان مفهوم العنصرية ومصادرها ومرتكزات علاجها عند بديع الزمان النورسي. ولتحقيق أهداف الدراسة، عمد الباحث إلى استخدام المنهج الوصفي التحليلي، الذي انتهى إلى أن العنصرية اعتداء على الآخرين، وتحدث التصادم المؤدي إلى الدمار والهلاك، وتعد تحديا لأوامر الله سبحانه وتعالى.\ أما مرتكزات علاجها فتتمثل بالدعوة إلى قراءة التاريخ البشري، ثم بيان حكم الشرع في العنصرية. وطرح البديل الإسلامي المتمثل بالأخوة الإسلامية، وأخيرا كشف حقيقة العنصرية المعادية للإسلام والمسلمين بل للإنسانية جمعاء. The study aims to describe the concept of racism, its sources and foundations for treatment in the view of Badde’ Al-Zaman Al-Norsi.\ In order to achieve the objectives of the study, the researcher used the descriptive analysis. The study concluded that racism is aggression on others, and leads to destruction and loss. It is also a challenge to the orders of Allah the Almighty. The foundations for treatment are manifest in the call\ for reading human history and deciding its legal status and proposing the Islamic alternative that is represented in the spirit of Islamic brotherhood.\ Finally, the research aims at uncovering the reality of racism and clarifying the fact that racism is against not only Islam and Muslims, but also against all humanity.
Keywords: الآداب الإسلامية; النورسي، سعيد، ت. 1960 م; الوعظ والإرشاد; الدعوة الإسلامية; العنصرية; المصلحون المسلمون